Exploring Excessive Working Hours Among Transportation Gig Workers in Indonesia - Aulia Widyarini; Devanto Shasta Pratomo; Sri Muljaningsih (Universitas Negeri Semarang, 2025)
The development of information technology has driven the emergence of the gig economy, which has significantly changed the employment landscape. In Indonesia, the gig economy's growth has led to a significantly increasing number of gig workers, particularly in the transportation sector. While digital platforms create flexible job opportunities, this work model also presents challenges, particularly excessive working hours, often necessary to meet daily income targets. This study analyzes the determinants of excessive working hours of gig workers in the transportation sector using logistic regression analysis with the 2022 National Labour Force Survey (Sakernas) data. The results confirm that gig workers in the transportation sector are likelier to experience excessive working hours than non-gig transportation workers. This finding proves that gig transportation workers are more vulnerable than traditional transportation workers. Several factors, such as gender, age, education, region, marital status, and ownership of a Kartu Prakerja, significantly influence the likelihood of gig workers in the transportation sector experiencing excessive working hours. The study’s findings offer implications for labor policies and social protection, particularly in ensuring the well-being of gig workers in the transportation sector amid the dynamics of the digital economy